2015
DOI: 10.1128/jvi.00546-15
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dengue Virus NS4A Protein Oligomerization

Abstract: Flavivirus NS4A protein induces host membrane rearrangement and functions as a replication complex component. The molecular details of how flavivirus NS4A exerts these functions remain elusive. Here, we used dengue virus (DENV) as a model to characterize and demonstrate the biological relevance of flavivirus NS4A oligomerization. DENV type 2 (DENV-2) NS4A protein forms oligomers in infected cells or when expressed alone. Deletion mutagenesis mapped amino acids 50 to 76 (spanning the first transmembrane domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 41 publications
2
50
0
1
Order By: Relevance
“…These observations suggest that RTN3.1A may interact with NS4A within the ER membrane, thus protecting NS4A from subsequent ER-associated degradation. One possible explanation is that RTN3.1A aids in the oligomerization of NS4A, as some recent reports have indicated that the oligomerization of DENV-2 NGC NS4A is mediated via the first TM domain (Lee et al, 2015;Stern et al, 2013), the domain potentially responsible for RTN3.1A-NS4A interaction. We are currently exploring this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that RTN3.1A may interact with NS4A within the ER membrane, thus protecting NS4A from subsequent ER-associated degradation. One possible explanation is that RTN3.1A aids in the oligomerization of NS4A, as some recent reports have indicated that the oligomerization of DENV-2 NGC NS4A is mediated via the first TM domain (Lee et al, 2015;Stern et al, 2013), the domain potentially responsible for RTN3.1A-NS4A interaction. We are currently exploring this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…NS4A is also predicted to form part of the replication complex (RC), determined from studies that have shown interactions with the replicative intermediates double-stranded RNA (dsRNA), NS1, NS2A, and NS5 (Mackenzie et al, 1998a) and via its interaction with the cellular scaffolding protein vimentin to aid RC formation (Teo and Chu, 2014). Additionally, mutations within the conserved amino acid and TM domains of NS4A impacted negatively on NS4A protein stability, cleavage efficiency, and oligomerization and duly on virus replication Mackenzie, 2011a, 2015;Stern et al, 2013;Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Significant evidence indicates that infection with (+) RNA viruses including DENV leads to the formation of membranous compartments called replication complexes, which operate as platforms where all required factors for viral RNA replication are concentrated [17]. The NS4A protein is the only viral factor directly associated with membrane rearrangement associated with DENV through its oligomerization [18]. Teo et al, 2013 reported that vimentin and its interaction with NS4A are important for the anchorage of replication complexes; also, vimentin reorganization and phosphorylation is fundamental to maintain the replication complexes structure[19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The pXJ vector (40), which contains a cytomegalovirus (CMV) promoter and multiple restriction enzyme sites (EcoRI, NotI, BamHI, XhoI, and KpnI), was used to construct the plasmids that transiently expressed NS2A and NS3 proteins. To ensure the correct topology of NS2A expressed in the ER, a leader sequence that contained the signal peptide of Gaussia luciferase (SPG) and the last 16 amino acids of NS1 (NS1 C16 ) were fused in frame to the N terminus of NS2A by overlap PCR (41,42).…”
mentioning
confidence: 99%